2016
DOI: 10.1016/j.jct.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of long-chain 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquids

Abstract: The heat capacities in the temperature range (5 to 370) K and the parameters of solid-phase phase transitions and fusion were determined for three [Cnmim][NTf2] (n = 10, 14, 16) ILs. The temperature-dependent vapour pressures of [C14mim][NTf2] and [C16mim][NTf2] were measured with a Knudsen effusion apparatus combined with a quartz crystal microbalance. Thermodynamic properties of these compounds in the crystal, liquid, and gas states were derived from the obtained data. The results obtained in this work were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…In addition, a number of further IL data have been provided by the National Institute of Standards and Technology [262]. In the meantime, a number of recent papers have been published presenting further heat-capacity data of ILs [263,264,265,266,267,268,269,270,271,272,273,274,275,276,277,278,279,280,281,282,283,284,285,286,287].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a number of further IL data have been provided by the National Institute of Standards and Technology [262]. In the meantime, a number of recent papers have been published presenting further heat-capacity data of ILs [263,264,265,266,267,268,269,270,271,272,273,274,275,276,277,278,279,280,281,282,283,284,285,286,287].…”
Section: Resultsmentioning
confidence: 99%
“…Quantum mechanical and statistical thermodynamic calculations on ionic vapour neutral ion pairs have been used to obtain gas-phase heat capacities for [C n C 1 Im][NTf 2 ] ( n = 2, 4, 6, 8) [ 139 ]. Correlations developed from these values have then been used to obtain Δ g l C p for [C n C m Im][NTf 2 ] ILs, ranging from Δ g l C p = −112 J K −1 mol −1 for [C 2 C 1 Im][NTf 2 ] to Δ g l C p = −203 J K −1 mol −1 for [C 10 C 10 Im][NTf 2 ] [ 129 , 130 , 132 , 133 , 135 ]. Clearly, there are very large and unsatisfactory discrepancies between these Δ g l C p values and the widely used Δ g l C p = −100 J K −1 mol −1 value; these differences can lead to significant variation in Δ vap H values, up to 20 kJ mol −1 for ILs with long alkyl chains [ 111 ].…”
Section: Measuring the Cohesive Energy Density For Ionic Liquids: Ovementioning
confidence: 99%
“…For ILs, both Knudsen effusion [ 56 , 86 89 , 91 , 119 , 129 133 , 135 , 151 , 152 ] and Langmuir [ 31 , 57 , 63 , 64 , 71 77 , 80 , 96 , 106 128 ] vaporization methods have been used to obtain Δ vap H . For Langmuir (i.e.…”
Section: Measuring the Cohesive Energy Density For Ionic Liquids: Ovementioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the work reported until now is mainly related to imidazolium- or pyridinium-based ILs combined with [Cl] − , [BF 4 ] − , [PF 6 ] − , or [NTf 2 ] − . Despite of the intense research, many data found in the literature are not of the highest quality due to the use of different experimental methodologies (e.g., scanning rates, annealing periods, sample size, thermal history, and sample purity). It is well accepted that ILs are structured fluids due to the complexity of their organization and diversity of the nature of their molecular interactions, showing high- and low-charge density regions. The understanding of the nanostructuration of ILs and its intrinsic relation to most of their physicochemical properties is fundamental to achieve the possibility of tuning an ionic liquid to a specific functionality or application without endless screening and trial and error. The effects of nanostructuration have been detected in several physicochemical properties, such as heat capacities, , densities, surface tensions, , viscosities, , thermal behavior, ,, and vapor pressures, among others . For all these properties a trend shift was observed at the same critical value for the number of carbons of the alkyl chain N = 6, named as the critical alkyl size (CAS). ,,,,, Pyridinium based ILs have a high potential of applicability , due to their high thermal stability and the aromatic character of the cation, exhibiting physical-chemical properties very similar to those of the imidazolium cation analogues. Nevertheless, the replacement of the imidazolium by the pyridinium cation modifies the structural organization of the liquid phase, affecting the physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%